Shock from Graying : Is the Demographic Shift Weakening Monetary Policy Effectiveness - Imam, Patrick (IMF Working Papers; Working Paper ;, 2013)
Abstract Empirical evidence is mounting that, in advanced economies, changes in monetary policy have a more benign impact on the economy-given better anchored inflation expectations and inflation being less responsive to variation in unemployment-compared to the past. We examine another aspect that could explain this empirical finding, namely the demographic shift to an older society. The paper first clarifies potential transmission channels that could explain why monetary policy effectiveness may moderate in graying societies. It then uses Bayesian estimation techniques for the U.S., Canada, Japan, U.K., and Germany to confirm a weakening of monetary policy effectiveness over time with regards to unemployment and inflation. After proving the existence of a panel co-integration relationship between ageing and a weakening of monetary policy, the study uses dynamic panel OLS techniques to attribute this weakening of monetary policy effectiveness to demographic changes. The paper concludes with policy implications.